Abdominal normothermic regional perfusion in donation after circulatory death: a systematic review and critical appraisal - van de Leemkolk, FEM; Schurink, IJ; Dekkers, OM; Oniscu, GC; Alwayn, IPJ; Ploeg, RJ; de Jonge, J; Huurman, VAL (Lippincott, Williams & Wilkins, 2020)
Background. Abdominal normothermic regional perfusion (aNRP) for donation after circulatory death is an emerging organ preservation technique that might lead to increased organ utilization per donor by facilitating viability testing, improving transplant outcome by early reversal of ischemia, and decreasing the risk of unintentional surgical damage. The aim of the current review is to evaluate the recent literature on the added value of aNRP when compared to local standard perfusion technique.